Bonded: Legacies of Captivity and Fugitivity from Enslavement to Incarceration in the Cape - Perez, Javier Ernesto (Department of Sociology, 2023)
The contemporary hyper-incarceration of ‘Coloured' South Africans is re-situated within the broader historical dialectics of racialisation and creolisation, traversing from colonial slavery to the modern prison regime. This study uses theorisations of marronage, fugitivity, and hauntology to posit novel understandings of the links between runaway slaves (‘droster1 gangs') and the contemporary ‘Coloured' criminal figure. This dissertation approaches the latter as engaged in traditions of opacity-making, initiated by the former as a production of complex structures of density and unknowability against the epistemic violence of the colonial gaze that seeks to ‘discover', categorise and control. As such, this study proposes to understand collectives of fugitives beyond the lexicons of criminality, on the one extreme, and resistance, on the other. Applying emerging qualitative and arts-based methods, it further offers an innovative methodological framework to strategically listen for the poetics and sonicity of fugitive narratives, highlighting the incondensable movements therein of dense temporalities, opacities, and personal and collective narration. Specifically, through a poetry- and performance-based workshop series, this study collaborates with formerly-incarcerated men to engage with the Cape's history of slavery and marronage, exploring the meanings and relevance of this history through creative writings, group discussions, and performance.